Occurrence of Bruquine (Coleoptera: Bruchidae) in Seeds of Emmotum nitens (Benth.) Miers (Research, Society and Development, 2021)
Emmotum nitens (Benth.) Miers, popularly known as Sobre, Carvalho-do-Cerrado, Salgueiro, among others, belongs to the family Icacinaceae, is widely dispersed in the Cerrados of Brazil, being one of the most important species. The beetles of the subfamily Bruchidae (Chrysomelidae) are important seed predators, mainly of legumes, and their larvae feed exclusively on seeds, mainly attacking the embryo. the objective of this work was to elucidate the oviposition, development and complete cycle of beetles of the subfamily Bruchidae in fruits and seeds of E. nitens. A percentage of 47% of fruits with the presence of oviposition on the external face (exocarp) and 21.4% of seeds predated by these bruchines were observed. After their complete cycle, adult beetles emerge through the hole present in the wall of the mesocarp. Its cycle time and urges take around six months.